Population genomics of Gymnogeophagus labiatus and G. lacustris reinforces the role of hydrographic isolation between evolutionary lineages (Cichlidae: Geophagini) - Figueiredo, Pedro Ivo C. C.; Hashimoto, Diogo T. [UNESP]; Ariede, Raquel B. [UNESP]; Zani, André L. S.; Varal, Maikel; Malabarba, Luiz R.; Fagundes, Nelson J. R. (FapUNIFESP (SciELO), 2025)
Abstract Gymnogeophaguslabiatus and G. lacustris represent a pair of sister taxa distributed in the Patos Lagoon (ELP) and Tramandaí-Mampituba (ETM) ecoregions in Southern Brazil and Uruguay. While G. lacustris was traditionally considered endemic to the ETM, G. labiatus has been assigned to both ecoregions, being distinguished from G. lacustris by its hypertrophied lips, which represent an adaptation for foraging in rocky environments, and by the variation in coloration. A recent study using mtDNA and morphological data challenged this interpretation and suggested that G. labiatus is exclusive of ELP, and that all individuals in ETM should be considered G. lacustris. In this work we used genome-wide ddRADseq markers to evaluate the evolutionary relationships between these species. The results corroborated early findings that each ecoregion harbors an independent evolutionary lineage, and that all individuals in ETM correspond to G. lacustris. Our results do not show significant genetic structure between riverine and lacustrine populations in ETM. However, we found evidence for secondary contact between G. labiatus and the riverine population of G. lacustris, suggesting that the hypertrophied lips in both groups may have a common genetic background, and may indicate an instance of adaptive introgression. Resumo Gymnogeophagus labiatus e G. lacustris representam um par de espécies irmãs distribuídas nas ecorregiões da Laguna dos Patos (ELP) e Tramandaí-Mampituba (ETM), no sul do Brasil e no Uruguai. Enquanto G. lacustris tem sido considerada endêmica da ETM, G. labiatus tem sido associada a ambas ecorregiões, sendo distinta de G. lacustris por seus lábios hipertrofiados, que representam uma adaptação para o forrageio em ambientes rochosos, além de variação na coloração. Um estudo recente que usou dados morfológicos e de mtDNA questionou essa interpretação, sugerindo que G. labiatus seria exclusivo da ELP, e que todos os indivíduos na ETM deveriam ser considerados G. lacustris. Nesse trabalho, usamos marcadores genômicos ddRADseq para avaliar a relação evolutiva entre essas espécies. Os resultados corroboraram achados anteriores de que cada ecorregião abriga uma linhagem evolutiva independente, e que todos os indivíduos na ETM correspondem a G. lacustris. Nossos resultados não evidenciam uma estrutura genética significativa entre as populações lacustres e fluviais na ETM. Entretanto, encontramos evidências de um contato secundário entre G. labiatus e as populações fluviais de G. lacustris, sugerindo que os lábios hipertrofiados em ambos os grupos podem ter uma base genética comum, podendo indicar um exemplo de introgressão adaptativa.